Surgical Management of Basilar Artery Laceration Caused by Transorbital Penetrating Injury: Case Report - Brenke, Christopher; Fontana, Johann; Schmieder, Kirsten; Barth, Martin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Transorbital penetrating injuries are rare and present with a heterogeneity of intracranial injury patterns that require individualized therapeutic procedures. In this report, we describe the case of a distal basilar artery laceration in a 16-month-old boy caused by accidental transorbital penetration with a pencil. Surgical removal of the pencil was performed, but hemostasis could only be achieved by clipping the impaired vessel. Adequate diagnostics and an individualized surgical strategy are necessary to deal with these life-threatening injuries.
Keywords: basilar artery; transorbital injury; surgical management